PENGARUH KOMPETENSI DAN TEKANAN ANGGARAN WAKTU TERHADAP KINERJA AUDITOR di KANTOR AKUNTAN PUBLIK (KAP) JAKARTA SELATAN - Heni Yusnita; Melva Juniati Simanjuntak (Jurnal Akuntansi dan Bisnis Krisnadwipayana, 2022)
The purpose of this study was To know and analyze the competence of the auditors performance at the Accountant Public South Jakarta, To know and analyze the time budget pressure of the auditors performance at the Accountant Public South Jakarta, and to know and analyze the competence and time budget pressure of the auditors performance at the Accountant Public South Jakarta. Methods of determining the sample used in this study is purposive sampling, while the data processing method used is multiple regression analysis. Data was collected by distributing questionnaires to 40 auditors at Office Accountant Public South Jakarta. The results of this study support the first hypothesis that the competence variable has a significant effect on the performance of auditors at the Accountant Public South Jakarta.   The results of this study support the second hypothesis that the time budget pressure variable has a significant effect on auditor performance at the Office Accountant Public South Jakarta.   And the results of this study support the third hypothesis that the competence variable and time budget pressure have a significant effect on auditor performance at the Office Acountant Public South Jakarta.